2005
DOI: 10.1002/uog.2624
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fetal lung volume assessed by three‐dimensional sonography

Abstract: Objective To determine the accuracy and precision of prenatal three-dimensional (3D) 84.86 (range, 57.30-99.48)% in cases with CDH and 91.38 (range,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
12

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 39 publications
3
79
0
12
Order By: Relevance
“…Total and contralateral fetal lung volumes can be measured precisely on 3DUS [23,24] correlating significantly with neonatal deaths [21,24] . Total fetal lung can be calculated using the rotational technique (VOCAL TM ) by summing the right and left lung volumes [19][20][21][22][23] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Total and contralateral fetal lung volumes can be measured precisely on 3DUS [23,24] correlating significantly with neonatal deaths [21,24] . Total fetal lung can be calculated using the rotational technique (VOCAL TM ) by summing the right and left lung volumes [19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Total and contralateral fetal lung volumes can be measured precisely on 3DUS [23,24] correlating significantly with neonatal deaths [21,24] . Total fetal lung can be calculated using the rotational technique (VOCAL TM ) by summing the right and left lung volumes [19][20][21][22][23] . Initial results showed that an observed/expected total fetal lung volume ratio (o/e-TotFLVR) lower than 0.35 was significantly associated with neonatal deaths [21] , confirming the results of previous studies using MRI [15][16][17][18] .…”
mentioning
confidence: 99%
“…Others [2,3,13] performed multiple measurements ranging from two to five measurements of each object, without a clear explanation for the repetition of the measurements. It is expected that multiple measurements will even out, and thus reduce the measurement error.…”
Section: Methodsmentioning
confidence: 99%
“…Both methods overestimated the actual volume, but all measurements had an error of less than 4%. Ruano et al [3] compared 3D measurements of lung volume with the VOCAL technique and post-mortem volume measurements of the fetal lungs. These authors reported that the VOCAL technique produced accurate volume measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation